Bridging yield gaps and doubling income of cashew growers in Karnataka - D.L. Maheswar, G. Basavaraj,; S. Anil Kumar, Mantesh Nandikoppa,; T.R. Guruprasad, Ashok S. Alur and (Journal of Plantation Crops, 2018)
Due to insufficient supply of raw cashew for processing and export demand, dependability on import of raw nuts has increased. Though there is huge potential for domestic demand and exports, the supply is plagued by several constraints. Low productivity has been a major constraint. Hence, the research study looks at productivity levels of cashew, across agro-climatic zones of Karnataka, a state aimed to become the largest producer of cashew by 2020. Yield gap analysis was carried out with an objective to understand, analyse and to suggest measures to bridge yield gaps and enhance income of the cashew growers. Findings from the research indicate wide yield gaps across all the agro-climatic zones in Karnataka. Evidence from the research indicated yield gaps are primarily due to nonadoption of recommended package of practices. Hence, suggestionsare made to strengthen extension activity on creating awareness on adoption of improved cultivation practices to bridge yield gaps and enhance farmer’s income.